2013
DOI: 10.1002/ajmg.a.36146
|View full text |Cite
|
Sign up to set email alerts
|

Bilaterally cleft lip and bilateral thumb polydactyly with triphalangeal component in a patient with two De novo deletions of HSA 4q32 and 4q34 involving PDGFC, GRIA2, and FBXO8 genes

Abstract: We report on a newborn boy with a bilateral cleft of the primary palate, duplicated triphalangeal thumbs, and a patent foramen ovale. During childhood he had moderate developmental delay. Brain MRI at 4 years was normal. The concurrence of non-syndromic clefts of the lip/palate (CL/P) and duplicated thumbs with triphalangeal component has, to our knowledge, not been reported so far. In our case, array-CGH analysis documented two de novo deletions (∼1.2 Mb and ∼400 Kb) of the long arm of chromosome 4, containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…For GRIA2, a wide variety of causative defects have been described. These include missense [7,31], nonsense [7,32], frame shift, truncation, splice site and in-frame deletion variants [7], as well as haploinsufficiency [7,[33][34][35]. Of the ten GRIA2 missense variants that have been functionally examined, six were reported to be LoF, three displayed behavior indistinguishable from that of wild-type, while one (a variant at the Q/R site) led to the production of Ca 2+ -permeable GluA2-containing receptors [7].…”
Section: Gria Disordermentioning
confidence: 99%
“…For GRIA2, a wide variety of causative defects have been described. These include missense [7,31], nonsense [7,32], frame shift, truncation, splice site and in-frame deletion variants [7], as well as haploinsufficiency [7,[33][34][35]. Of the ten GRIA2 missense variants that have been functionally examined, six were reported to be LoF, three displayed behavior indistinguishable from that of wild-type, while one (a variant at the Q/R site) led to the production of Ca 2+ -permeable GluA2-containing receptors [7].…”
Section: Gria Disordermentioning
confidence: 99%
“…Combined loss of both PDGFRα-specific ligands, PDGFA and PDGFC, results in facial clefting (Ding et al 2004). In humans, mutations in and around PDGFC (Choi et al 2009; Calcia et al 2013) and PDGFRα (Rattanasopha et al 2012) have been associated with cleft lip and palate (CL/P), reflecting a conserved role for PDGF signaling in mammalian midface development. Interestingly, NCC conditional loss of FGF receptor 1 (FGFR1) also results in craniofacial defects (Trokovic et al 2003; Wang et al 2013), indicating a requirement for both PDGF and FGF signaling in NCCs for craniofacial morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Pdgfc deletion studies in mice have also revealed that PDGF-CC is essential for palatogenesis (Ding et al, 2004). Interestingly, human linkage and association studies show strong linkage between a 30-cM region on human chromosome 4, where the PDGFC gene maps, or the rs28999109 polymorphism in the PDGFC promoter and occurrence of cleft lip with or without cleft palate (CL/P) (Choi et al, 2009; Marazita et al, 2002), which suggests that PDGF-CC has role a in palatogenesis also in humans (Calcia et al, 2013; Choi et al, 2009; Jugessur et al, 2009). …”
Section: Pdgf-cc Structure and Mechanisms Of Activationmentioning
confidence: 99%